Islamic Education Learning Management using the Wordwall Application in Tahsin and Tajwid Programs at Daarul Armina Foundation - Winda Herlina; Malinda Musfika Rahayu; Yupita Sari; Fitria Meilinda; Dalima Septiria (JMiE (Journal of Management in Education), 2024)
Learning the Qur'an, especially tahsin and tajwid, plays a strategic role in shaping students' religious competence. However, learning tahsin and tajwid in Islamic educational institutions still faces various obstacles, such as conventional learning methods, low learning motivation, and students' difficulties in understanding the abstract concept of tajwid. This study aims to describe the implementation of the Wordwall application in tahsin and tajwid learning at the Daarul Armina Foundation and analyze its impact on students' motivation and learning engagement. This study uses a qualitative descriptive approach with tahsin and tajwid teachers and students as research subjects. Data collection techniques include observation, in-depth interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions, with data validity maintained through triangulation of sources and techniques. The results of the study indicate that the implementation of Wordwall through the stages of planning, content development, implementation, and evaluation is able to create more interactive tahsin and tajwid learning, increase learning motivation, and make it easier for students to understand the makharijul huruf and the laws of tajwid. Thus, Wordwall can be an effective and relevant digital learning medium in learning the Qur'an in the digital era.